APPLICATION OF INTELLIGENT CONTROL SYSTEMS (SMART GRID) IN IMPROVING ENERGY EFFICIENCY IN MICROELECTRIC NETWORKS AND THEIR ECOLOGICAL ECONOMIC ANALYSIS (Modern American Journal of Engineering, Technology, and Innovation, 2026)
This article explores the issues of increasing energy efficiency and minimizing losses in microgrids based on photovoltaic systems within the infrastructure of Chirchik State Pedagogical University. The research aims to evaluate the economic and environmental efficiency of modernizing an educational institution's energy system using Smart Grid technologies. Modeling results conducted in the HOMER Pro software environment demonstrate that the implementation of intelligent management systems reduces energy losses by 20-22% and increases cost-efficiency by 35%. The conclusions presented in this article serve as a practical foundation for designing "green" energy systems in higher education institutions of Uzbekistan.